SISTEM PERENCANAAN PEMBIAYAAN ANGGARAN DALAM RANGKA MENDUKUNG PELAKSANAAN PENDIDIKAN - Muddin, Sanniati; Musfirah, Musfirah; Suban , Alwan (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The budget financing planning system is an important element in supporting the implementation of quality and sustainable education. This research aims to design and develop a system that is able to integrate the planning, allocation and supervision processes of education budgets efficiently and transparently. This approach includes needs analysis, preparation of a system framework, and implementation of information technology to support data-based decision making. By utilizing a systematic methodology, this research produces a budget planning model that is responsive to educational needs, accommodates the dynamics of policy change, and supports the involvement of various stakeholders. The results of this system are expected to increase the efficiency of resource management, reduce the potential for budget irregularities, and encourage equal access to education. These findings provide a significant contribution in supporting the government's efforts to achieve inclusive and sustainable national education development goals.